Effect of chiral ligand concentration and binding mode on chiroptical activity of CdSe/CdS quantum dots - Garcia Melchor, Max; Gounko, Iouri (My University, 2019)
Chiroptically active fluorescent semiconductor nanocrystals, quantum dots (QDs), are of high interest from a theoretical and technological point of view, because they are promising candidates for a range of potential applications. Optical activity can be induced in QDs by capping them with chiral molecules, resulting in circular dichroism (CD) signals in the range of the QD ultraviolet–visible (UV-vis) absorption. However, the effects of the chiral ligand concentration and binding modes on the chiroptical properties of QDs are still poorly understood. In the present study, we report the strong influence of the concentration of a chiral amino acid (cysteine) on its binding modes upon the surface of CdSe/CdS QDs, resulting in varying QD chiroptical activity and corresponding CD signals. Importantly, we demonstrate that the increase of cysteine concentration is accompanied by the growth of the QD CD intensity, reaching a certain critical point, after which it starts to decrease. The intensity of the CD signal varies by almost an order of magnitude across this range. Nuclear magnetic resonance and Fourier transform infrared data, supported by density functional theory calculations, reveal a change in the binding mode of cysteine molecules from tridentate to bidentate when going from low to high concentrations, which results in a change in the CD intensity. Hence, we conclude that the chiroptical properties of QDs are dependent on the concentration and binding modes of the capping chiral ligands. These findings are very important for understanding chiroptical phenomena at the nanoscale and for the design of advanced optically active nanomaterials.
PUBLISHED
Keywords: Chirality; Quantum dots; Chiroptical activity; Cysteine; Ligand concentration; Binding mode; Density functional theory; Nanoscience & Materials